2021
DOI: 10.1155/2021/8874516
|View full text |Cite
|
Sign up to set email alerts
|

The Generation and Modulation of Distinct Gamma Oscillations with Local, Horizontal, and Feedback Connections in the Primary Visual Cortex: A Model Study on Large-Scale Networks

Abstract: Gamma oscillation (GAMMA) in the local field potential (LFP) is a synchronized activity commonly found in many brain regions, and it has been thought as a functional signature of network connectivity in the brain, which plays important roles in information processing. Studies have shown that the response property of GAMMA is related to neural interaction through local recurrent connections (RC), feed-forward (FF), and feedback (FB) connections. However, the relationship between GAMMA and long-range horizontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…This suggests that MG might be related to local E-I in the input layer [ 65 73 ], while LG might be related to horizontal connections in the output layer, which has long-distance connections on a larger spatial scale. The distinct mechanisms of LG and MG are consistent with the model prediction from a recent computational study [ 34 ]. The involvement of different neural circuits in V1 gamma rhythms also explains the finding that each gamma rhythm has a specific relationship to the spike activity ( S5 Fig ) and suggests that different gamma bands might be related to different neural functions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This suggests that MG might be related to local E-I in the input layer [ 65 73 ], while LG might be related to horizontal connections in the output layer, which has long-distance connections on a larger spatial scale. The distinct mechanisms of LG and MG are consistent with the model prediction from a recent computational study [ 34 ]. The involvement of different neural circuits in V1 gamma rhythms also explains the finding that each gamma rhythm has a specific relationship to the spike activity ( S5 Fig ) and suggests that different gamma bands might be related to different neural functions.…”
Section: Discussionsupporting
confidence: 88%
“…Our study also showed that there are spike–LFP phase locking for the low and medium GCs in V1. According to previous studies on 2 gammas in V1 [ 33 , 34 ], the spatial scale of the communication for LG and MG might be different. LG generated in superficial layer of V1 might have a relative larger communication scale than that of MG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An obvious candidate to explain our observations is the system of long-range horizontal cortical connections which are excitatory but terminate on inhibitory as well as excitatory neurons (Ajima and Tanaka, 2006;Kurt et al, 2008). In line with this idea, modeling work suggested differential roles of horizontal, feedback and feedforward connections for gamma oscillations depending on gamma frequency (Han et al, 2021). The activation of horizontally projecting layer II/III neurons has been shown to elicit repetitive inhibitory as well as excitatory postsynaptic potentials in the gamma frequency range (Adesnik and Scanziani, 2010).…”
Section: Functional Role Of Inter-columnar Vs Intra-columnar Generated Gamma Oscillationsmentioning
confidence: 64%
“…We therefore speculate that both gamma responses play distinct roles during acoustic processing. It is noteworthy that two types of gamma oscillations with different tuning properties were also observed in the visual system (Jia et al, 2011;Han et al, 2021). Relatedly, in slices of the auditory cortex Ainsworth and colleagues (Ainsworth et al, 2011) could show that even individual columns contain two gamma rhythm generators with different oscillation frequencies.…”
Section: Functional Role Of Inter-columnar Vs Intra-columnar Generated Gamma Oscillationsmentioning
confidence: 97%